El incremento injustificado de precios de los alimentos que se expiden en los establecimientos comerciales, violan la Ley Orgánica de Defensa del Consumidor - Cabrera Orellana, Harthman Demetrio (2016)
This work is framed within the guidelines established by the National University of Loja; the issue under discussion is the unjustified increase in prices of food purchased at stores, violate the Organic Law of consumer protection, to whose study we considered general objective: "Make a critical study of the Organic Law on Defense Consumer, to propose solutions to the problem. " In order to achieve this, we made use of several scientific methods, in research processes, such as: inductive, deductive, analytical, statistical, etc .; as well as apply a survey of 20 lawyers; from whom we obtained valuable results as the fact that most respondents said that lack of control allows speculation on prices, which not only involved in the economic drive of the country, but causes serious problems in the social aspect due to the lack of resources to meet the needs of all citizens. This thesis concludes with the presentation of the proposal to reform the Organic Law of Consumer Protection, this being the result of the analysis of all data obtained during the research process